Characterisation of high-performance cold bitumen emulsion mixtures for surface courses - Nassar, Ahmed I.; Mohammed, Mahmoud khashaa; Thom, Nicholas; Parry, Tony (Taylor & Francis, 2016)
Cold bitumen emulsion mixture (CBEM) is not yet widely used as a surface course around the world. In this study, 0/14-mm-size dense-graded surface course CBEMs have been investigated. The mechanical performance was evaluated in terms of stiffness modulus over 3 months and resistance to permanent deformation under three different stress levels (100, 200, 300 kPa), whilst durability evaluation was carried out in terms of resistance to moisture and frost damage. The study has also investigated the incorporation of low cement content (1%) with relatively sustainable by-product fillers, namely ground-granulated blast furnace slag (GGBS) and fly ash (FA) type 450-S on both mechanical and durability performance. A comparison has been carried out between the low and high cement content CBEM, as well as with respect to corresponding hot mix asphalt (HMA). The results revealed that the incorporation of GGBS and FA in CBEMs leads to superior performance, similar to CBEMs treated with high cement content and comparable to an equivalent HMA. Furthermore, GGBS replacement exhibited better performance than that of FA replacement. The findings suggest that the new sustainable types of CBEM can be developed for using as a surface layer for medium- to heavy-trafficked roads.